MENCIUM MUSHAF AL-QUR’AN DALAM TRADISI MASYARAKAT MUSLIM: SEBUAH TRANSMISI DAN TRANSFORMASI: MENCIUM MUSHAF AL-QUR’AN DALAM TRADISI MASYARAKAT MUSLIM: SEBUAH TRANSMISI DAN TRANSFORMASI - Liyna Nabilata, Lub (AR-ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2023)
This paper tries to explain how the phenomenon of kissing the Mushaf of the Qur'an in the tradition of Muslim society. One of the cultural behaviors of the Muslim community is kissing the Koran after reading it or when getting a manuscript of the Koran in an obsolete (less respectable) place. This also applies to the yellow books (turats). This phenomenon is seen through the perspective of reception theory. In this realm the Qur'an is at a practical stage, namely how the theological side of the Qur'an is able to give birth to a unique practical form in the Al-Qur'an tradition, people have the belief that the Qur'an is the word of God which is qadim. In this phenomenon, transmission and transformation are found. As for the transmission of the reception of kissing the Mushaf of the Qur'an, it came from fiqh literature and adab al-Qur'an, the next transmission of which was to kiss the Mushaf of the Qur'an in the era of the companions, as was done by the companion of Ikrimah bin Abu Jahal. The transformation process is found in the form of the background and the purpose of kissing the Al-Qur'an Mushaf which is also related to the object.